Sino-North Korean Ideological Relations in Face of 20th Congress of the Communist Party of China - Kierasiński, Mariusz (HAPSc Policy Briefs Series, 2022)
The aim of this paper is to analyze the most important aspects of the ideological relations between the People’s Republic of China (PRC) and the Democratic People’s Republic of Korea (DPRK) in the face of the 20th Congress of the Communist Party of China (CPC). The Policy Brief is divided into four parts: Reactions of the Workers’ Party of Korea to the 20th Congress of the Communist Party CPC; Mention of Korea during the 20th CPC Congress; The role of CPC in People’s Republic of China according to WKP and the Significance of Sino-North Korean ideological relations after 20th Congress of the CPC. The methodology included media and literature review, which were collected through Korean Central News Agency, Rodong Sinmun and documents of the 20th Congress of the CPC. This study makes evident the importance of ideological relations between China and North Korea.